Pharmacokinetics of ganciclovir and valganciclovir in the adult horse. Issue 5 (10th January 2013) - Carmichael, R. J.; Whitfield, C.; Maxwell, L. K.
Abstract : Equine herpes myeloencephalopathy, resulting from equine herpes virus type 1 (EHV‐1) infection, is associated with substantial morbidity and mortality in the horse. As compared to other antiviral drugs, such as acyclovir, ganciclovir has enhanced potency against EHV‐1. This study investigated the pharmacokinetics of ganciclovir and its oral prodrug, valganciclovir, in six adult horses in a randomized cross‐over design. Ganciclovir sodium was administered intravenously as a slow bolus at a dose of 2.5 mg/kg, and valganciclovir was administered orally at a dose of 1800 mg per horse. Intravenously administered ganciclovir disposition was best described by a three‐compartment model with a prolonged terminal half‐life of 72 ± 9 h. Following the oral administration of valganciclovir, the mean observed maximum serum ganciclovir concentration was 0.58 ± 0.37 μg/mL, and bioavailability of ganciclovir from oral valganciclovir was 41 ± 20%. Superposition predicted that oral dosing of 1800‐mg valganciclovir two times daily would fail to produce and maintain effective plasma concentrations of ganciclovir. However, superposition suggested that i.v. administration of ganciclovir at 2.5 mg/kg every 8 h for 24 h followed by maintenance dosing of 2.5 mg/kg every 12 h would maintain effective ganciclovir serum concentrations in most horses throughout the dosing interval.